PERSONAL ARCHIVE MANAGEMENT WITH DIGITAL CURATION CONCEPT ON STUDENTS’ SMARTPHONES - Sembiring, Santana; Khairunnisa, Khairunnisa; Kurnia, Leila (Record and Library Journal, 2019)
Bckground of the study: Digital curation activities are necessary for organizing digital archives to be accessible to the present and future. The problem in this research is that information and library management (MIP) students who have previously received records management (MRA) courses through digital curation have not fully implemented digital curation in managing digital archives.Purpose: This study aims to find out how MIP students curate digital archives of their photos and documents on the smartphone.Method: The method used in this research is a qualitative descriptive approach and technique. Data used in interviews with five MIP students as informants.Findings: The results show that information in conducting digital curation activities such as digital object evaluation and discussion, life cycle and digital object management on an ongoing basis, and keeping them accessible, each individual has a unique and different way.Conclusion: Factor needs, memories, and usefulness of digital archive become a more determining factor in students in digital curation.